Lean resource management and reliable interaction for a low-carbon-oriented new grid - Liu, Yuting (Frontiers in Energy Research, 2024)
The lean resource management and reliable interaction of massive data are important components of low carbon-oriented new grid. However, with a high-proportion of distributed lowcarbon resources connected to new grid, the issues such as data anomalies, data redundancy, and data missing lead to inefficient resource management and unreliable interaction, affecting the accuracy of power grid decision making as well as effectiveness of emission reduction and carbon reduction. Therefore, this paper proposes a lean resource management and reliable interaction framework of middle platform based on distributed data governance. On this basis, a distributed data governance approach for lean resource management method of middle platform in low-carbon new grid is proposed, which realizes anomaly data cleaning and missing data filling.Then, a data storage and traceability method for reliable interaction is proposed, which prevents the important data from being illegally tampered within the interaction process. Simulation results demonstrate that the proposed algorithm significantly enhances efficiency, reliability, and accuracy in anomaly data cleaning and filling as well as data traceability.